Interrogative Particles in Arabic and English: A Comparative Analysis of Their Semantic Features (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Interrogative particles are fundamental to constructing questions and facilitating information exchange in any language. This article investigates the semantic features of interrogative particles in Arabic and English, examining their usage, function, and contextual nuances. Although both languages utilize interrogative particles to seek information, their syntactic positions, morphological structures, and semantic scopes differ significantly due to the structural diversity of Semitic and Germanic language families. By analyzing native texts, spoken discourse, and grammatical frameworks, this study highlights the intricate role of these particles in expressing certainty, politeness, emphasis, and formality. The comparative analysis provides valuable insights for linguists, language learners, and translators aiming to understand cross-linguistic variation and pragmatic interpretation in interrogative forms.